2015
DOI: 10.1161/circep.114.001672
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Follow-Up After Catheter Ablation of Persistent Atrial Fibrillation Using the Stepwise Approach and Prognostic Factors for Success

Abstract: A total of 549 patients with persAF underwent CA using the stepwise approach at our institution in 2007 to 2009. Of these, 493 © 2015 American Heart Association, Inc. Original Article Circ Arrhythm ElectrophysiolBackground-In the meantime, catheter ablation is widely used for the treatment of persistent atrial fibrillation (AF). There is a paucity of data about long-term outcomes. This study evaluates (1) 5-year single and multiple procedure success and (2) prognostic factors for arrhythmia recurrences after c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(112 citation statements)
references
References 47 publications
5
95
1
5
Order By: Relevance
“…U takich pacjentów ablacja przezcewnikowa jest bardziej skuteczna niż farmakoterapia antyarytmiczna [185,586,713,[717][718][719][720]. W randomizowanych próbach klinicznych, w których oceniano ablację jako leczenie pierwszego rzutu u pacjentów z napadowym AF, wykazano jedynie nieco lepsze wyniki pod względem utrzymywania rytmu zatokowego w porównaniu z farmakoterapią antyarytmiczną [585,[721][722][723].…”
Section: Wskazaniaunclassified
See 1 more Smart Citation
“…U takich pacjentów ablacja przezcewnikowa jest bardziej skuteczna niż farmakoterapia antyarytmiczna [185,586,713,[717][718][719][720]. W randomizowanych próbach klinicznych, w których oceniano ablację jako leczenie pierwszego rzutu u pacjentów z napadowym AF, wykazano jedynie nieco lepsze wyniki pod względem utrzymywania rytmu zatokowego w porównaniu z farmakoterapią antyarytmiczną [585,[721][722][723].…”
Section: Wskazaniaunclassified
“…Początkowo PVI zbadano u pacjentów z napadowym AF, ale wydaje się, że również w przetrwałym AF jest to metoda nie gorsza niż bardziej rozległa ablacja [729,735]. U pacjentów z przetrwałym AF wykonywano także bardziej rozległe zabiegi ablacji, ale nie ma wystarczających danych, by obecnie sformułować zalecenia dotyczące ich wykonywania [117,718,719,[735][736][737]. Rozległe zabiegi ablacji (wykraczające poza PVI) zawsze wymagają dłuższego czasu trwania zabiegu i większej ekspozycji na promieniowanie jonizujące, co potencjalnie stwarza zagrożenie dla pacjentów.…”
Section: Metody I Technologieunclassified
“…In contrast, 2 large registries reported single-procedure success rates of only 35.3% and 47.8% at 12 months. 16,17 The recently published single-center randomized CHASE-AF trial (Randomized Catheter Ablation of Persistent Atrial Fibrillation Study) investigated the stepwise approach (termed full defragmentation) versus standalone PVI in patients with persistent AF. The trial could not demonstrate a difference in arrhythmia recurrence during 12 months of follow-up; a higher incidence of AT as the mode of recurrence was observed in the full defragmentation group.…”
Section: Current Ablation Strategies For Chronic Afmentioning
confidence: 99%
“…Several single-arm registries reported that conversion of AF (to SR or AT) during ablation impacted positively on longterm clinical success, 16,17,[20][21][22] whereas others, including the randomized CHASE-AF trial, did not demonstrate a beneficial impact of AF conversion. 11,15 In our analysis, conversion of AF was not associated with a superior clinical outcome.…”
Section: Conversion Of Af and Arrhythmia Recurrencementioning
confidence: 99%
“…1 While the cornerstone of CA of paroxysmal AF is pulmonary vein (PV) isolation, catheter-based treatment of persistent and long-standing persistent arrhythmia varies across centers and among electrophysiologists. Different schools of thought have proposed and tested various approaches: staged approach, 2 linear ablation lines, 3 ablations of fractionated potentials, 4 ganglionic plexi ablation, 5 elimination of low-voltage areas in the left atrium (LA), 6 ablation of focal impulses and rotors, 7 or different combinations, which were driven mainly by unsatisfactory results reported for ablations, in general. The multicenter randomized STAR-AF II trial (The Substrate and Trigger Ablation for Reduction of Atrial Fibrillation Trial Part II) found no reduction in the rate of AF recurrence when PV isolation, in patients with persistent AF, was supplemented with linear ablations or ablations of complex fractionated electrograms.…”
mentioning
confidence: 99%